Pengaruh Kepemimpinan Situasional dan Supervisi Kepala Madrasah Madrasah terhadap Kinerja Guru Madrasah Aliyah di Propinsi Papua Barat - Effendi M (Institut Agama Islam Negeri (IAIN) Manado, 2016)
This study aims to analyze and examine (1) the relationship of the principal situational leadership with teachers’ performance, (2) the relationship of principal supervision with teachers’ performance, and (3) the relationship of principal situational leadership and supervision all together with the performance of teachers at Madrasah Aliyah in West Papua. This study uses a survey with correlation technique. Research conducted in the province of West Papua, which consists of six districts or cities: Sorong, Manokwari, Fakfak, Raja Ampat, Kaimana, and Sorong. Samples are selected in proportion taking the proportion of the population of teachers in each district or city into account. Data are collected using a questionnaire and analyzed using statistical correlation (simple and double), calculating the coefficient of determination, and testing the significance of the partial correlation. The results show that (1) there is a positive correlation between the teachers’ performance and principal situational leadership; (2) there is a positive relationship between principal supervision and teachers’ performance; and (3) there is a significant relationship and influence of situational leadership and supervision of the principal on teachers’ performance at Madrasah Aliyah in West Papua. In other words, increasing the effectiveness of situational leadership and supervision of the principal would have a positive influence on improving the performance of teachers in the madrassas.